THE EFFECT OF RETURN ON ASSETS (ROA), CAPITAL INTENSITY AND CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE TO TAX AGGRESSIVENESS (International Journal of Psychosocial Rehabilitation, 2020)
Background Lanis and Richardson in Atami and Kurnia (2017) states that the act of tax aggressiveness is the desire to minimize the tax burden through legal, illegal or both ways. Efforts to minimize tax pay can be through aggressive tax actions such as tax planning, tax avoidance and tax evasion. The company made the policy to reduce the amount of tax be paid.Phenomenon of tax aggressiveness occurred in one of the big mining companies in Indonesia. Danang Sugianto (2019) states that Global Witness reports that PT Adaro Energy Tbk has performed a tax trick with Transfer Pricing through its Singapore subsidiary, Coaltrade Services International. These efforts have been carried out from 2009 to 2017.Secretary General of FITRA, Yenny S (2017) states that tax evasion is a serious problem in Indonesia. It is suspected that each year there is Rp 110 trillion, which is a tax avoidance figure. According to him, "most of them are business entities engaged in the mineral and coal sector. Most are also foreign companies. There are also Indonesian legal entities, but their ownership is actually foreign”Another phenomenon was conveyed by the Tax Justice Network Institute that PT Bentoel International Investama Tbk (Bentoel Group) practices tax avoidance in Indonesia, the impact the country could suffer a loss of US $ 14 million per year. (Benedicta Prima, 2019)